Whither Neurotheology? - Klemm, W. R. (Religions, 2019)
Human culture has modernized at a much faster pace than has theology and religion. We are at the point where many moderns apparently think that religion is losing relevance. Satisfying the need for relevance and ecumenical harmony requires more reasoned and mature approaches to religion. Science is one of those secular activities that seems to undermine religious faith for many people. Unlike the sciences that give us the Big Bang, relativity, quantum mechanics, and theories of evolution, neuroscience is the one science that applies in everyday life toward developing a faith that promotes nurturing of self and others. Modern neuroscience and the mental health understanding that it creates can contribute to satisfying this need. Neuroscience and religion have numerous shared areas of concern, and each worldview can and should inform and enrich the other. Neuroscience may help us understand why we believe certain religious ideas and not others. It helps to explain our behavior and might even help us live more righteous and fulfilled lives. Religion can show neuroscientists areas of religious debate that scientific research might help resolve. New educational initiatives at all levels (secondary, seminary, and secular college) can provide a way to integrate neuroscience and religion and lead to religious perspectives that are more reasoned, mature, satisfying, and beneficial at both individual and social levels. Neurotheology is an emerging academic discipline that seems to focus on integrating neuroscience and theology. About only 10 years old, neurotheology has not yet consolidated its definition, ideology, purpose, or scholarly or applied strategies. Acceptance by the scholarly community is problematic. This manuscript raises the question of whether neurotheology will survive as a viable discipline and, if so, what form that could take.